Associations among Primary Stability, Histomorphometric Findings, and Bone Density: A Prospective Randomized Study after Alveolar Ridge Preservation with a Collagen Cone - Sigmar Schnutenhaus; Werner Götz; Jens Dreyhaupt; Heike Rudolph; Ralph G. Luthardt; Cornelia Edelmann (MDPI AG, 2020)
Background: The objective of this investigation was to examine whether determination of bone density (BD) with a cone beam computed tomography (CBCT) scan could help predict the primary stability (PS) of the implants and to investigate whether associations between the histomorphometric findings and the CBCT scan could be observed. Materials and methods: In this randomized clinical study, the efficacy of alveolar ridge preservation (ARP) with a combination of a collagen cone and a collagen membrane procedure after tooth extraction was investigated. CBCT scans were obtained after a healing period of 8 (±1) weeks. Subsequently, the CBCT scans were evaluated in terms of BD at different heights of the former socket. Eleven (±1) weeks after tooth extraction, implant placement was performed and PS was measured with resonance frequency analysis. Potential associations among the radiologically measured BD, the histomorphometric results, and the PS were analyzed. Results: No direct association was observed between the radiologically determined BD and the histomorphometric findings. No significant associations could be found between the BD and the PS. Conclusion: No significant associations were observed among the BD determined by the CBCT, the histomorphometric findings, and the PS.